Heavy metal accumulation during the last 30 years in the Karnaphuli River estuary, Chittagong, Bangladesh - Wang, Ai-jun (Springerplus, 2016)
Heavy metal contamination of aquatic environment has attracted global attention owing to its abundance, persistence, and environmental toxicity, especially in developing countries like Bangladesh. Five heavy metals, namely chromium (Cr), copper (Cu), nickel (Ni), lead (Pb) and zinc (Zn) were investigated in surface and core sediments of the Karnaphuli River (KR) estuary in Chittagong, Bangladesh, in order to reveal the heavy metal contamination history in estuarine sediments and its response to catastrophic events and human activities. The surface sediment was predominantly composed of silt and sand, and the surface sediment was contaminated with Cr and Pb. Based on the (210)Pb chronology, the sedimentation rate in the inter-tidal zone of KR estuary was 1.02 cm/a before 2007, and 1.14 cm/a after 2008. The core sediment collected from 8 to 20 cm below the surface mainly originated from terrestrial materials induced by catastrophic events such as cyclone, heavy rainfall and landslides in 2007 and 2008. The values of contamination factor (CF) showed that the sediment became moderately contaminated with Cr and Pb in the last 30 years. The variation and accumulation of heavy metals in core sediment before 2000 was mainly related to natural variations in sediment sources; however, in subsequent years, the anthropogenic inputs of heavy metals have increased due to rapid physical growth of urban and industrial areas in the Chittagong city. In general, the accumulation pattern of heavy metals after normalization to Aluminum in sediments of KR estuary indicated an accelerated rate of urbanization and industrialization in the last 30 years, and also suggested the influence of natural catastrophic event on estuarine environment.